Postoperative Delirium (POD) in Cancer Patients its Incidence and Risk Factors a Prospective Observational Study - Shah Qasim, Xu-Ying Li, Tao Wei, Khalid Khan, Qaisar Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In cancer patients, surgery is an essential part of the multimodality treatment to remove solid tumors and nearly 50% of the cancer patients underwent surgery for the treatment of cancer usually experienced post-operative delirium (POD). Currently, screening for delirium in the surgical wards at many cancer hospitals in China isn’t the component of everyday clinical care. Objectives: This study aims to examine the existing situation of suspected post-operative delirium in cancer patients undergoing surgery during the first 72 hours after surgery, and to identify the risk factors associated with postoperative delirium (POD). Study Design: Prospective/observational study Place and Duration: Hunan cancer Hospital. 1st December 2019 and 31st December 2019 Methods: Chinese Cancer patients scheduled for surgery, aged 18 years or elders were prospectively observed by bedside nurses for 03 consecutive postoperative days for the presence of delirium by using Nursing delirium screening scale (Nu-DESC Chinese version). Results: Among the 319 included cancer patients, 39 (12.2%) developed suspected POD. Univariate analysis showed that cancer surgical patient with comorbidity of hypertension and chronic hepatitis, surgical specialty, duration of surgery >3 hours, post-operative use of benzodiazepine and opioids to be significantly associated with suspected POD. Binary logistic regression model showed hypertension (OR 7.857 95% CI 3.484–17.718 p=<.001), chronic hepatitis (OR 44.087 95% CI 2.517–772.3 p=0.01), and duration of surgery >3 hours (OR 2.908 95% CI 1.285–6.580 p=0.01), to be independent risk factors for occurrence of suspected POD. Conclusion: The 12.2% incidence of suspected postoperative delirium (POD) in cancer patients is significant. Recognizing of cancer patients by the nurses and clinicians who may be at risk for developing POD and addressing the modifiable risk factors are extremely essential to lower the risk of its developing. Keywords: Delirium; Postoperative delirium; Cancer; risk factors; Nu-DESC